Ethnomedicinal uses of plants among the Newar community of Pharping village of Kathmandu District, Nepal - Balami, N. P. (Tribhuvan University Journal, 2006)
The present paper highlights 119 species of plants used as medicine by the Newar community of Pharping village of Kathmandu district. All reported medicinal plants were used for 35 types of diseases like Diabetes, Epilepsy, Fever, Jaundice, Rheumatism and other condition such as incense, spice and flavourant etc. Key words: Ethnomedicine, Newar, Pharping village, Kathmandu district.